Correlated electron photoemission: old problems, emerging thrusts and opportunities for theory - Allen, J.W. (Physica. B, Condensed matter, 2005)
The k-resolved spectral function for electron addition and removal is a basic theoretical tool for characterizing strongly correlated electron systems. Subject to certain qualifications the removal part can be measured by angle resolved photoemission spectroscopy. An overview is given of recent photoemission work on old problems, on emerging thrusts of experimental effort and on new opportunities for meaningful comparison of experiment to theory for strongly correlated electron systems.